Impolitic Gambling. Chance and Inequality in Contemporary Italy - Di Chio, Sabino (PARTECIPAZIONE E CONFLITTO, 2017)
The liberalization of gambling is a measure equally taken and implemented by both sides with-in the bipolar system that typified Italian politics over the years 1990-2000. For 25 years, the growing number of operators, players and betting opportunities has been blessed as a "necessity", a forced deci-sion that does not respect the reference values represented by the political forces that have in turn been part of the ruling majorities. The assumption of this paper is that the financial and regulatory consolidation path of the "lawful game" provides, both from the governmental and cultural viewpoint, a privileged indi-cation to describe the depoliticization of the Second Italian Republic compared to the conflict that should have raged within it as a competitive democracy. From the government viewpoint, the elected institutions renounced the political direction of the field to support the neo-liberal axioms that consider the accuracy of public accounting, the encouragement of consumption and the transfer of public assets to private capitals as three indisputable methods to pursue economic growth. From a cultural viewpoint, the silent consensus of Italian voters for gambling seems to reflect a more general consensus for the "chance" factor, the tolerance for uncertainty that deeply per-meates Italy as the other neo-capitalist societies.